PENGAJARAN MATEMATIKA DENGAN PENDEKATAN INTERAKTIF - Hasratuddin Hasratuddin (Study Program of Mathematics Education of Unimed Postgraduate Program, 2008)
This study aims to: 1) design a model of interactive teaching on the topic of linear equations in one variable SMP; 2) designing effective mathematics instruction using an interactive model on the topic of linear equations in one variable junior; 3) Describe the learning outcomes of students on the topic of a single linear equation variables through a model of interactive teaching in secondary schools. The population in this study is the first class of junior high students as much as six grade 35 Medan. Samples taken at random one class of grade I-4 were 39 students consisting of 22 male students and 17 female students. Type of data in this study are the result of student learning, learning design, and data observations. Instruments in this research is in the form of tests and questionnaires. Analysis of data about the effectiveness of the learning process used in the study were statistically analsis infrensial, while data on the questionnaire (attitude) of students used the descriptive statistical analysis. The results found that: 1) the model of mathematics learning is a form of problem solving interktif cooperatively with the steps; organizing group, the presentation of issues, facilitate discussion, and summarizing; 2) student learning outcomes classically found that exhaustiveness is 89.74% and student attitude towards learning by achieving percentage of 82.05%, so that learning is found effective.